(untitled) (Bangladesh Journal of Medicine, 2013)
A case-control study conducted in the Department of Dermatology and Venereology of Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2008- December 2010. A total 60 female patients of telogen effluvium attending in outpatient department (OPD) were enrolled in the study with 30 having hair loss considered as case (Group-A) and another 30 females had no history of hair loss were considered as control (Group-B). The study included 60 patients and the mean age were 25.4±7 years ranging from 18 to 42 years in group A and 24.8±5.6 years ranging from 17 to 36 years in group B. Maximum number was found in the age group of 21- 30 years in both groups and nearly three fourth (73.4%) patients were unmarried in group A and 18(60.0%) in group B. Most of the patients were student in both groups, which were 21(70.0%) and 17(56.7%) in group A and group B respectively and majority of the the patients were HSC level in both groups, 15(50.0%) and 14(46.7%) in Group A and Group B respectively. Most of the patients came from middle class, which were 20(66.7%) and 16(53.3%) in group A and group B respectively. The mean serum ferritin were 18.8±8.1 g/L ranging from 4.5 to 36.54 g/L and 36.6±9.9 mg/L ranging from 18.46 to 56.3 mg/ L in group A and group B respectively. The mean Hb level was 11.5±1.4 gm/dl ranging from 8.5 to 14.0 gm/dl in group A and 12.8±1.1 gm/dl ranging from 10.5 to 14.5 gm/dl in group B. The mean difference of Hb level was statistically significant (p<0.05) between two groups in unpaired t-test. It can be concluded that low iron level is associated with telogen effluvium in women. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13617 Bangladesh J Medicine 2010; 21: 84-89